Modelling Quality Of Life Hypertensive Patient - Koerniawan, Dheni; Frisca, Sanny (UKMC International Conference (UKMC IC) Proceedings, 2024)
Hypertension (HT) still become silent killer disease leading to mortality. Although many efforts and programs of HT increase blood pressure control, but internal factors such as age, gender, duration of illness (DOI), attitude, medication adherence (MA), routine check-up (RCU), and blood pressure (BP) still play important role to enhancing blood pressure control and even more so the quality of life (QoL) hypertensive patients. This research aims to testing a hypothetic modelling of previous research to find an internal factors model of QoL in hypertensive patients. Cross-sectional study used to 89 samples randomize due to online questionnaire collecting data. Correlation used to eliminate variables which did not significant adding to the model. Then model testing by partial-least square analysis. The result shows that attitude directly affect the MA and RCU significantly, also MA to BP and BP to QoL, but interestingly did not significant in RCU to BP. As addition, it has significant effect as attitude to BP through MA, MA to QoL through BP, and so simultaneously attitude to QoL with MA and BP as intervening. So, it becomes very important as nurses to empower patient’s attitude to manage and maintain their lifestyle with their hypertensive condition to enhance their adherence in medication so they blood pressure in controlled and will have a good quality of life.